2010
DOI: 10.1177/1057567710368362
|View full text |Cite
|
Sign up to set email alerts
|

A Culturally Nuanced Test of Gottfredson and Hirschi’s ‘‘General Theory’’: Dimensionality and Generalizability in Japan and the United States

Abstract: The current research addresses two specific issues that direct attention to the relatively neglected topic of the cross-cultural applicability of Gottfredson and Hirschi's ''general theory'' that has been developed in and tested primarily in the United States. With theoretical and empirical guidance from the literature on dimensionality of low self-control, we first predict that the six elements identified in the theory form a multidimensional latent construct in two diverse societies-Japan and the United Stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
13
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 49 publications
(79 reference statements)
2
13
0
Order By: Relevance
“…This finding suggests that impulsivity may not be as important in Ghana as it often appears in western studies, a finding that reinforces conclusions from self-report studies in nonwestern societies (Cheung & Cheung, 2008;Kobayashi et al, 2010). The unique and consistent relation between academic difficulties and juvenile delinquency highlight the importance of the school context and how juveniles' experiences with this institution are relevant to their behavior.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This finding suggests that impulsivity may not be as important in Ghana as it often appears in western studies, a finding that reinforces conclusions from self-report studies in nonwestern societies (Cheung & Cheung, 2008;Kobayashi et al, 2010). The unique and consistent relation between academic difficulties and juvenile delinquency highlight the importance of the school context and how juveniles' experiences with this institution are relevant to their behavior.…”
Section: Discussionsupporting
confidence: 83%
“…As recent studies elsewhere are beginning to show the influence of even "established" variables, such as impulsivity and low self-control, on delinquency can vary depending on the context. Kobayashi, Vazsonyi, Chen, and Sharp's (2010) comparative study of students from Japan and the United States revealed a weak relationship between low self-control and deviance in the Japanese context compared with the United States. Maldonado-Molina, Piquero, Jennings, Bird, and Canino, (2009) reported similar findings in a study of juveniles from Bronx in New York and San Juan in Puerto Rico in relation to sensation seeking and exposure to violence and frequent juvenile offending.…”
Section: Research On Risks and Correlates Of Juvenile Delinquencymentioning
confidence: 87%
“…See, for example, Aranha and Burress (2010), Chen (2004), Cheung and Cheung (2008), Kobayashi et al (2010), Liu (2011), Messner (2014), and Yun and Walsh (2011). …”
mentioning
confidence: 99%
“…According to SAT, crime causation ultimately entails a "perception-choice 1 The utility of comparing Asian and Western societies to develop criminological theory given the pronounced institutional and cultural differences has been widely recognized. See, for example, Aranha and Burress (2010), Chen (2004), Cheung and Cheung (2008), Kobayashi et al (2010), Liu (2011), Messner (2014, and Yun and Walsh (2011). 2 The research in cross-cultural psychology reviewed below focuses primarily on contrasts between the West and the East Asian societies of China, Japan, and Korea.…”
Section: Synopsis Of the Theorymentioning
confidence: 99%